2015
DOI: 10.1002/eji.201545495
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of HCMV‐specific immune responses: Parallels between CD8+ T cells, CD4+ T cells, and NK cells

Abstract: CD8+ T cells are important for immunity against human cytomegalovirus (HCMV). The HCMV-specific CD8 IntroductionUpon viral infection the immune system engages lymphocytes such as NK cells, CD4 + and CD8 + T cells to eliminate the virus. CD4+ and CD8 + T cells recognize viral peptides presented by MHC class II (MHC-II) and MHC class I (MHC-I) molecules respectively. CD8 + T cells specific for the infecting pathogen first undergo massive expansion before they differentiate into cytotoxic cells capable of produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 131 publications
3
30
0
1
Order By: Relevance
“…As illustrated in Figure , we also observed a considerable number of individuals with a high number of CD4 + CD57 + and CD4 + CD27 − T cells that could not be ascribed to aging alone, in contrast to CD8 + T cells where only a proportion (<30%) of healthy individuals display a steady increase in their proportions during aging. The accumulation of differentiated CD4 + T cells has been observed previously and may also result from latent viral infections such as described for their CD8 + counterpart , but may also be caused by Th2 driven responses in unreported allergies or other subclinical conditions, which was not examined among our participants.…”
Section: Discussionmentioning
confidence: 68%
“…As illustrated in Figure , we also observed a considerable number of individuals with a high number of CD4 + CD57 + and CD4 + CD27 − T cells that could not be ascribed to aging alone, in contrast to CD8 + T cells where only a proportion (<30%) of healthy individuals display a steady increase in their proportions during aging. The accumulation of differentiated CD4 + T cells has been observed previously and may also result from latent viral infections such as described for their CD8 + counterpart , but may also be caused by Th2 driven responses in unreported allergies or other subclinical conditions, which was not examined among our participants.…”
Section: Discussionmentioning
confidence: 68%
“…Typically, exhausted T cells fail to control viral infection as they have effector defects (Wherry, 2011) including loss of proliferative potential, decreased cytotoxicity, impaired ability to secrete cytokines (Frebel et al, 2010; Wherry and Kurachi, 2015), and sustained high expression of several inhibitory receptors (e.g., PD1, KLRG1, and CD57) (Blackburn et al, 2009). Although HCMV-specific CD8 + T cells also have low proliferative capacity and express senescence markers, such as KLRG1 and CD57 (Vieira Braga et al, 2015), they are not exhausted as they are still highly cytotoxic and produce Th1 cytokines in response to sporadic viral re-activation (Klenerman and Oxenius, 2016). In addition, molecular profiling of HCMV-specific CD8 + T cells has demonstrated that PD-1, an inhibitory receptor associated with T cell dysfunction, is expressed at very low levels in healthy individuals (Vieira Braga et al, 2015).…”
Section: Human CMV Infection Memory Inflation and Immunosenescencementioning
confidence: 99%
“…Although HCMV-specific CD8 + T cells also have low proliferative capacity and express senescence markers, such as KLRG1 and CD57 (Vieira Braga et al, 2015), they are not exhausted as they are still highly cytotoxic and produce Th1 cytokines in response to sporadic viral re-activation (Klenerman and Oxenius, 2016). In addition, molecular profiling of HCMV-specific CD8 + T cells has demonstrated that PD-1, an inhibitory receptor associated with T cell dysfunction, is expressed at very low levels in healthy individuals (Vieira Braga et al, 2015). Therefore, persistent HCMV infection does not induce massive exhaustion of the T cell repertoire in most immunocompetent individuals.…”
Section: Human CMV Infection Memory Inflation and Immunosenescencementioning
confidence: 99%
“…However, NK cells can also contribute as effector cells to adaptive immune responses by mediating antigen-specific antibody-dependent cellular cytotoxicity (ADCC) [2,3] and producing IFN-γ in response to interleukin-2 (IL-2) secreted by antigen-specific CD4 + T cells [2,[4][5][6][7]. Moreover, it is recognized that NK cells undergo intrinsic transformation as a result of infection or inflammation [3,[8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%